COVID-19 Coronavirus Infection and Trimesters: Is There a Link? - Gulbanu Ganikyzy Shaimerdenova; Gulzhan Abuova; Dana Bekaryssova (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Objectives: Despite serious challenges, humanity has been able to adapt and take measures to limit the spread of COVID-19 and minimize its negative consequences. This pandemic has emphasized the importance of global collaboration, scientific and medical progress, and raised questions about the need to strengthen health systems and international crisis response mechanisms. Although humanity continues to face new challenges associated with COVID-19, including the emergence of new strains, the development and introduction of vaccines and effective therapeutic agents have raised hope for overcoming the pandemic and creating a more sustainable health system for the future. The aim of our study was to investigate the course of the disease according to trimesters. Material and methods: We retrospectively analyzed the case histories of women with COVID-19 coronavirus infection treated in the mentioned hospitals between December 2020 and February 2022. The study considered the following parameters according to the trimester of pregnancy: number of previous pregnancies, age, disease severity and presence of comorbidities. Results: Mild COVID-19 accounted for a smaller proportion of the sample (3.2-13%) due to treatment at home or in outpatient settings. More than half of those hospitalized (209- 51.0%) were admitted in severe condition. Analysis of COVID-19 severity distribution by trimester showed statistically significant differences (p<0.05). Associated diseases were detected in 306 patients, accounting for 74.6% of all cases. Statistically significant differences were found when evaluating comorbidities according to trimester. The main complaints included dry cough (394), weakness (388), sore throat (372), fever (367), malaise (365) and headache (287). Conclusions: Infection is more frequently observed in pregnant women in the third trimester, which may be related to the increased frequency of diagnosis in this period. The presence of comorbidities is a factor that increases the severity of the condition.